(untitled) (Al-Aasar, 2025)
The term "Khair" (خير) in the sayings of Prophet Muhammad ﷺ carries a profound and multifaceted meaning, encompassing various aspects of faith, worship, ethics, and social conduct. In Islamic teachings, Khair is not limited to material goodness but extends to spiritual, moral, and communal well-being. The Prophet ﷺ used this term to describe the excellence of a believer, the virtues of knowledge and understanding of religion, and the significance of acts of worship such as prayer, charity, and striving in the way of Allah. Furthermore, Khair is associated with good manners, kindness, and honorable social interactions, emphasizing justice, patience, and generosity. In the realm of daily life, it highlights the importance of honest labor, strong companionship, and financial responsibility. The diverse applications of Khair in prophetic traditions demonstrate its role as a guiding principle for a balanced and righteous life. This study explores the various dimensions of Khair in Hadith literature, illustrating how it serves as a comprehensive framework for personal and collective success in both this world and the hereafter.